PERANAN NOTARIS DALAM PROSES PEMBUBARAN PERSEROAN TERBATAS MENURUT UNDANG-UNDANG NOMOR 40 TAHUN 2007 - , Rosdiana; , Dr. Sutanto, S.H., M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research is aimed to understand and study notaryâs role in the process of limited company dispersal based on law number 40 year 2007